Collaborative Projects: Unleashing Early Career Scientists' Power. (October 2019) - Bodmer, Pascal; Attermeyer, Katrin; Pastor, Ada; Catalán, Núria
Abstract : Collaborative research projects exclusively targeted to early career researchers (ECRs) have been initiated in Europe. So far, the first two collaborative projects have united more than 80 ECRs. We describe the structure and benefits of such initiatives for the ECRs and highlight the positive influence on the whole scientific community.